1997
DOI: 10.1046/j.1365-3040.1997.d01-52.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil CO2 concentration does not affect growth or root respiration in bean or citrus

Abstract: Contrasting effects of soil CO2 concentration on root respiration rates during short-term CO2 exposure, and on plant growth during long-term CO2 exposure, have been reported. Here we examine the effects of both short-and long-term exposure to soil CO2 on the root respiration of intact plants and on plant growth for bean (Phaseolus vulgaris L.) and citrus (Citrus volkainenana Tan. & Pasq.). For rapidly growing bean plants, the growth and maintenance components of root respiration were separated to determine whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 24 publications
4
40
1
Order By: Relevance
“…A slight decrease in the concentration of O 2 in the soil air does not inhibit root respiration (Palta and Nobel, 1989). The increase in the concentration of CO 2 in the soil air was also unremarkable, and no consistent effects of extremely high concentrations of CO 2 in soil air on the physiological activity of roots have been reported (Bouma et al, 1997;Qi et al, 1994). Thus, the earlier leaf senescence in the plants in the W pots does not seem to be caused by decline in physiological activities of roots owing to an oxygen defi cit.…”
Section: Discussionmentioning
confidence: 96%
“…A slight decrease in the concentration of O 2 in the soil air does not inhibit root respiration (Palta and Nobel, 1989). The increase in the concentration of CO 2 in the soil air was also unremarkable, and no consistent effects of extremely high concentrations of CO 2 in soil air on the physiological activity of roots have been reported (Bouma et al, 1997;Qi et al, 1994). Thus, the earlier leaf senescence in the plants in the W pots does not seem to be caused by decline in physiological activities of roots owing to an oxygen defi cit.…”
Section: Discussionmentioning
confidence: 96%
“…Irving et al suggested that waterlogging injury was caused the 15% of increasing in carbon dioxide accompany with 20% of decreasing in oxygen, in their pot experiment using lucerne [19]. In contrast, Bouma et al showed no toxic effect of carbon dioxide to root respiration and the elongation using bean plant [16]. In the experimental equipment, actually, the pH in Hypoxia treatment was significantly decreased in compared with Cont., and this may mean that the solution in Hypoxia was acidified by increasing carbon dioxide ( Table 2).…”
Section: Relationships Between Shoot Dry Matter and Pod Dry Mattermentioning
confidence: 96%
“…oxygen: 0% -21%, carbon dioxide: 0.03% -21% [15]. The origin of plant watterlogging injury has been understood as their condition, "low oxygen" [16] or "high carbon dioxide" [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Intact root respiration was measured for a short time (approximately 5 min; Fan et al, 2003;Zhu et al, 2005a). In this study, we assumed that the amount of natural soil and the respiration of microbes were the same in all cylinders (Bouma et al, 1997a(Bouma et al, , 1997b and used the intact root system plus medium respiration as a proxy for total root respiration. The intact root system respiration values were divided by the total root length obtained by WinRhizo scanning (described below) to obtain the specific root respiration per unit of root length (mmol CO 2 m 21 root length s 21 ).…”
Section: Root Respiration and Root Harvestmentioning
confidence: 99%